'They Are Not like […] Pamela Hódi […] Constantly Showing Off'—How Hungarian Tweens Negotiate Fame through Disney Princesses. Issue 2 (4th May 2022) - Zsubori, Anna
Abstract: Ever since Disney Princesses were established as a marketing brand in 2000, they have become a famous 'phenomenon' that has been commercially successful, popular, and adored, but one that has also received much criticism from scholars and consumers alike. Although audience research has gained increasing recognition in recent years, this field's attention has focused mainly on the 'West', neglecting Eastern European—including child—audiences. Moreover, while there are several scholarly examinations of Disney Princess films, these studies mainly employ textual analysis (Escalada-Cordova 2018; Whelan 2014; Wilde 2014) rather than conducting empirical research. Instead of reading for the audiences and making assumptions about how they interpret fame from a media text, in this case Disney Princesses, it is therefore crucial to ask audience members themselves, as Sonia Livingstone observes, 'it is established that audiences are plural in their decodings, that their cultural context matters, and that they often disagree with textual analyses' (2008, p. 4). By drawing upon diverse scholarly works within the field of celebrity studies as well as undertaking an audience study with Eastern European—specifically Hungarian—tweens, the objective of this article is twofold. On the one hand, this paper argues that animated characters are indeed entitled to have a fame status. It does so by deploying theorisations that distinguish between heroes and celebrities (North, Bland, and Ellis 2005), celebrities and stars (G. Turner, Bonner, and Marshall 2000), and differentiate among animated characters considered as 'celeactors' (Rojek 2001), or as stars (Ellis 2007; McGowan 2018; 2019). On the other hand, through the analysis of audiences' diverse perceptions of fame, illustrated by Hungarian tweens' understanding of Disney Princesses—an enormous global media phenomenon—this article provides a key case study for the aforementioned argument while highlighting the features of celebrity culture that are specific to Hungary. Taking into account Hungarian tweens' approaches towards Disney Princesses, while considering that Disney is claimed to have 'immense power over childhood culture' (Garofalo 2013) and that '[t]he celebrity is simultaneously a construction of the dominant culture and a construction of the subordinate audiences of the culture' (Marshall 2014, p. 48), this paper starts revealing the diverse ways in which different cultures conceptualise celebrity notions.